Three Dimensional mapping of the root apex: distances between apexes and anatomical structures and external cortical plates - Carlos Henrique FERRARI; Amjad ABU HASNA; Frederico Canato MARTINHO (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract This study aimed to determine the mean distances between apexes of the maxillary posterior teeth and the maxillary sinus, between apexes of the mandibular posterior teeth and the mandibular canal, and between the root apexes of all teeth and the adjacent cortical plates. A total of 800 cone-beam computed tomography (CBCT) scans (400 maxillary and 400 mandibular) were obtained from patients indicated for several treatments. The proximity between apexes and anatomical structures, and the relationship between apexes and adjacent cortical plates were assessed together with the risk of over-instrumentation. Paired-sample comparisons were performed by using the paired t-test. The means were compared by ANOVA, Kruskal-Wallis and Dwass-Steel-Critchlow-Fligner tests. a) Most of the apexes classified as A (high-risk proximity) were observed in maxillary first and second molars, in mandibular first and second molars, and in second premolars in relation to near anatomical structures. b) A predominance of class A (86.42%) was noticed in the first premolars, between apexes of maxillary teeth and adjacent cortical plates. c) The distance between apexes of mandibular teeth and buccal cortical plates showed a predominance of medium-risk proximity (B) in all the groups, except the first premolars, with the highest risk (82.22%), and the second molars, with low-risk proximity (C) to distal and mesiobuccal apexes (91.77% and 89.62%). CBCT images are important for endodontic diagnosis and treatment, since many teeth have high risk proximity to near anatomical structures and adjacent cortical plates.